2023
DOI: 10.1002/jcu.23558
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of lung and breast cancer brain metastases: Comparison of texture analysis and deep convolutional neural networks

Mehmet Ali Gultekin,
Abdusselim Adil Peker,
Ayse Betul Oktay
et al.

Abstract: PurposeMetastases are the most common neoplasm in the adult brain. In order to initiate the treatment, an extensive diagnostic workup is usually required. Radiomics is a discipline aimed at transforming visual data in radiological images into reliable diagnostic information. We aimed to examine the capability of deep learning methods to classify the origin of metastatic lesions in brain MRIs and compare the deep Convolutional Neural Network (CNN) methods with image texture based features.MethodsOne hundred for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…We have read with great interest the recently published study by Gultekin et al, who compared texture analysis and three different deep-learning models to differentiate lung and breast brain metastases (BM). 1 The deep learning architectures were based on convolutional neural networks (CNN) commonly used in image analysis and with extensive data sets. While the study has demonstrated the CNN models using radiomic features achieve excellent results, it has several critical limitations.…”
mentioning
confidence: 99%
“…We have read with great interest the recently published study by Gultekin et al, who compared texture analysis and three different deep-learning models to differentiate lung and breast brain metastases (BM). 1 The deep learning architectures were based on convolutional neural networks (CNN) commonly used in image analysis and with extensive data sets. While the study has demonstrated the CNN models using radiomic features achieve excellent results, it has several critical limitations.…”
mentioning
confidence: 99%